UPAYA PENGEMBANGAN KUALITAS SUMBER DAYA MANUSIA DALAM PELAYANAN KESEHATAN DI BALAI BESAR KESEHATAN PARU MASYARAKAT (BBKPM) MAKASSAR - Aswan Usman; Rifdan (SEMINAR NASIONAL DIES NATALIS 62, 2023)
This descriptive qualitative research aims to develop the quality of human resources in health services at the Makassar Community Lung Health Center (BBKPM). Primary data came from in-depth interviews and focus group discussions with 12 informants. Secondary data were sourced from official documents; development strategic plans, government agency performance accountability reports, annual reports and literature review. There are three stages in analyzing data, namely data reduction, data presentation, and conclusion drawing. The results showed that the condition of human resources at the Makassar Community Lung Health Center (BBKPM) was in accordance with the standards but still needed experts in certain fields. Efforts to develop the quality of HR are carried out by forming HR management which includes planning, provision and development stages. In development there are two methods. In-service methods are training, development, rotation, temporary assignments, and performance appraisal and appreciation programs. Out-of-service methods are executive development programs, practical training, and organizational development. This effort provides benefits for BBKPM Makassar in developing human resources in improving the quality of health services.